Ethno-diversity of Katarniaghat wildlife sanctuary - Singh, Rahul Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The floral diversity in the Wild Life Sanctuary is immense. The present documentation indicates the presence of 95 tree species. 57 shrubs. 28 climbers, and 23 species of grasses. The main tree species are Sal (Shorea robusta). Asna (Terminalia alata), Shisham (Dalbergia sissoo). Bel (Aegle marmelos), Kusum (Schleichera oleosa), Ficus spp and Semal (Bombax ceiba), etc. The main grass species occurring in the area are Kaans (Saccharum spontaneum) and Moonj (Saccharum munja). Calamus tern. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->